2019
DOI: 10.1002/anie.201901592
|View full text |Cite
|
Sign up to set email alerts
|

Isoselective Lactide Ring Opening Polymerisation using [2]Rotaxane Catalysts

Abstract: Polylactide (PLA) is a fully biodegradable and recyclable plastic, produced from a bio‐derived monomer: it is a circular economy plastic. Its properties depend upon its stereochemistry and isotactic PLA shows superior thermal‐mechanical performances. Here, a new means to control tacticity by exploiting rotaxane conformational dynamism is described. Dynamic achiral [2]rotaxanes can show high isoselectivity (P i =0.8, 298 K) without requiring any chiral additives and enchain by a chain end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“… [ 122 ] X Single-use infant feeding bottle. [ 127 ] X Biodegradable plastic product design. [ 138 ] X Thermo-chemical exploitation of plastic.…”
Section: Resultsmentioning
confidence: 99%
“… [ 122 ] X Single-use infant feeding bottle. [ 127 ] X Biodegradable plastic product design. [ 138 ] X Thermo-chemical exploitation of plastic.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the ring‐opening alternating copolymerization (ROAC) of anhydrides and epoxides and the ring‐opening polymerization (ROP) of lactones are much more desirable syntheses, which offer a controlled polymerization route to produce polyesters under mild conditions. [ 7 ] Based on this, a selective copolymerization strategy can be developed with the combination of ROAC and ROP, producing block polyesters from the mixture of monomers in a one‐pot strategy. [ 8 ] For example, Williams and co‐workers reported that a commercially available chromium salen catalyst can combine the ROAC of phthalic anhydride (PA)/propylene oxide (PO) and the ROP of L‐lactide (LA) to produce well‐defined ABA triblock polyesters.…”
Section: Methodsmentioning
confidence: 99%
“…Beer and co‐workers investigated the use of rotaxanes for the ring‐opening polymerisation (ROP) of rac ‐lactide (Scheme 7). [29] Their study was based on rotaxanes bearing a crown ether macrocycle and a thread featuring an ammonium station together with an additional thiourea or triazole moiety (Scheme 7 a). In the protonated form of the rotaxane, the macrocycle binds to the ammonium unit while in the deprotonated form, the macrocycle becomes weakly bound to the amine with the possibility of moving freely along the axle.…”
Section: Rotaxane‐based Organocatalystsmentioning
confidence: 99%